Bioinformatics Integrative Analysis of Circadian Rhythms Effects on Atopic Dermatitis and Dendritic Cells - Sun N; Dai D; Deng S; Cai X; Song P (Dove Medical Press, 2023)
Nan Sun,1 Dan Dai,1 Shihang Deng,2 Xun Cai,3 Ping Song1 1Department of Dermatology, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of China; 2Department of Dermatology, Shenzhen Bao'an Authentic TCM Therapy Hospital, Shenzhen, 518126, People's Republic of China; 3Department of Dermatology, The Fifth People's Hospital of Suzhou, Suzhou, 215131, People's Republic of ChinaCorrespondence: Nan Sun; Ping Song, Department of Dermatology, Guang'anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, 100053, People's Republic of China, Email dr-sue@foxmail.com; songping@vip.126.comBackground: Atopic dermatitis (AD) is an allergic inflammatory skin disease caused by aberrant and over-reactive immune response. Although circadian rhythm disruption is implicated in multiple immunoinflammatory conditions, including AD, the mechanisms at the molecular level underlying AD and circadian rhythms remain elusive.Methods: Bulk and single-cell RNA-sequencing data of AD patients were acquired from the Gene Expression Omnibus, including GSE121212, GSE120721, and GSE153760 datasets. A single-sample gene set enrichment analysis was performed to estimate circadian rhythm gene expression levels. A differential expression analysis was utilized to identify the key candidate genes in AD. CIBERSORT was used to quantify the proportions of immune cells, and the R package "Seurat" was utilized to investigate single-cell RNA-sequencing data.Results: Circadian rhythm gene expression levels were lower in AD skin samples than in normal skin samples. Dendritic cells were significantly upregulated and negatively correlated with circadian rhythm gene expression levels in AD patients. Compared with circadian rhythm-related genes in the control samples, ARNTL2, NOCT, and RORC were differentially expressed in AD; ARNTL2 and NOCT were significantly upregulated, whereas RORC was significantly downregulated in AD. ARNTL2, NOCT, and RORC also showed robust abilities to diagnose AD. We validated that the abundance of the dendritic cell was positively correlated with the ARNTL2 and NOCT expression levels using bulk RNA-sequencing data of the GSE121212 and single-cell RNA-sequencing data of the GSE153760. Moreover, the functional enrichment analysis showed that the IL-17 and NF-κB signaling pathways, Th1 and Th2 cell differentiations, and primary immunodeficiency, were enriched in AD patients.Conclusion: The findings of this study suggested that the circadian rhythm is involved in the progression of AD, and RNTL2, NOCT, and RORC as well as dendritic cells are differentially expressed in AD. These findings could be used to introduce diagnostic and chronotherapeutic modalities for AD.Keywords: atopic dermatitis, circadian rhythms, dendritic cells, ARNTL2, NOCT, RORC